Socialization of Strategies to Increase Sales of Processed Dairy Products at Mataram Milk as a Support for Animal Protein for the Community - Meireni Cahyowati; Ariya Dwi Nugrahanto; Harvey Febrianta; Indra Kurniawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The socialization of sales improvement strategies was held at Mataram Milk, which is an micro, small and medium enterprises in the Special Region of Yogyakarta Province which focuses on the field of milk processing such as pasteurized milk with various flavors, pudding and jamu milk. This socialization aims to provide knowledge, information and strategies in order to support the increase in sales of the products, especially Mataram Milk. The problems found in Mataram Milk are regarding product marketing, production equipment and distribution permits from the Food and Drug Supervisory Agency. Mataram Milk socialization activities were carried out at the Mataram Milk business location in the Special Region of Yogyakarta with the owner of Mataram Milk through 2 (two) methods, such as observation and socialization with resource persons regarding cow's milk processing material and sales strategies for dairy products. This socialization activity provides a positive response from the owners of Mataram Milk such as interactive discussions and business owners have a clear overview for sales strategies, BPOM distribution permit requirements, milk processing production equipment.